A FRAMEWORK FOR SITUATIONAL METHOD ENGINEERING USING ESSENCE STANDARD TO SUPPORT METHOD CHUNK SHARING AND METHOD COMPOSITION - Widyani, Yani
In Situational Method Engineering (SME), a situational method is composed of method chunks. Although there are advantages to applying SMEs, it does require extra effort. Method chunks are not easy to find. This research proposes a framework to guide method engineers to construct situational methods and for tools developers to build the supporting system. The proposed framework essentially lists the critical processes of SMEs. This research also proposes a method chunk metamodel in Essence Language, including the situational model. Using a standard notation will ease the extraction and composition of method chunks. The proposed framework applies an assembly-based process in the situational method construction process. We also adopt the concept of service-oriented by promoting three participants: the provider, the publisher, and the client. Our framework defines the complete processes, including the extraction of method chunks from any existing methods, publishing the method chunks, finding the method chunks, and constructing a situational method from selected method chunks. Detailed processes of the framework are designed based on the Essence. Therefore we call it the Essence-based SME framework (ESME framework). The ESME framework has been validated to ensure that the framework can assist method engineers in applying SMEs. The validation process consists of a) executing the proposed process manually; b) building the SME support system prototype; c) producing situational methods in Essence in several case studies; and d) representing several existing situational methods in Essence. The overall results of the validation process show that the ESME framework can assist method engineers in situational method engineering. Furthermore, comparing this research to similar research shows that this research result has some advantages on several indicators.